SOCIO-PHILOSOPHICAL AND PEDAGOGICAL BASIS OF THE CONCEPT OF TOLERANCE - Salokhov, A.; Qamariddinova, G.A. (Educational Research in Universal Sciences, 2023)
The article aims to reveal ways of pedagogical support for the young generation to be free from defects in the qualities of tolerance and tolerance, especially in the field of human relations, when they enter the scene of the world community. In order to understand the essence of tolerance, first of all, it is necessary to analyze the types of it and the relationship between them. It is impossible to achieve the intended goal if we try to cultivate religious or ethnic tolerance and forget about other types. Therefore, it is stated that a comprehensive approach is considered important in the formation and development of tolerance in the literal sense.